Drosophila Melanogaster Utilization in Genetics Lectures: Innovations that Need to be Optimized - Diani Fatmawati; Maryam Saleem; Iin Hindun; Indah Permatasari; Solikhah Solikhah; Diana Khoiroh; Ahmad Fauzi (JURNAL PENDIDIKAN SAINS UNIVERSITAS MUHAMMADIYAH SEMARANG, 2022)
Drosophila melanogaster is a popular model organism that plays a role in the development of Genetics research and learning. The purpose of this study was to map Genetics lecture activities in Indonesia based on the utilization of Drosophila melanogaster during practicum activities. The data was collected using Google Form-based questionnaire analyzed using descriptive statistical analysis. A total of 113 alumni from 39 universities in Indonesia were involved as participants. The results informed that 77% of institutions had conducted Genetic Practicums and more than half had used Drosophila melanogaster. However, optimizing the use of these organisms in learning needs to be improved because the use of Drosophila melanogaster is still limited to morphological, chromosome, life cycle, and inheritance pattern observations.